2010
DOI: 10.1002/adfm.201001081
|View full text |Cite
|
Sign up to set email alerts
|

Optical pH Sensor with Rapid Response Based on a Fluorescein‐Intercalated Layered Double Hydroxide

Abstract: The preparation of a highly oriented photoluminescent film of fluorescein (FLU) and 1‐heptanesulfonic acid sodium (HES) co‐intercalated in a layered double hydroxide (LDH) matrix by electrophoretic deposition (EPD) is reported, and its application as an optical pH sensor is demonstrated. The FLU‐HES/LDH films with thickness ranging from nanometer to micrometer on indium tin oxide substrates exhibite good c‐orientation of LDH platelets (the ab‐plane of the LDH platelets parallel to the substrate), as confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 68 publications
1
80
0
Order By: Relevance
“…Base on the example above, it can be known that the selection of a suitable fluorescent compound with high response to H + in solution is of great importance for fabricating pH-sensitive optical materials. Shi et al [55] have reported Journal of Nanomaterials a highly oriented photoluminescent film with film thickness of 300 nm based on the fluorescein and 1-heptanesulfonic acid sodium co-intercalated into LDH matrix. The film exhibits a broad linear dynamic range for solution with pH value from 5.02 to 8.54.…”
Section: Ph-responsive Luminescent Materialsmentioning
confidence: 99%
“…Base on the example above, it can be known that the selection of a suitable fluorescent compound with high response to H + in solution is of great importance for fabricating pH-sensitive optical materials. Shi et al [55] have reported Journal of Nanomaterials a highly oriented photoluminescent film with film thickness of 300 nm based on the fluorescein and 1-heptanesulfonic acid sodium co-intercalated into LDH matrix. The film exhibits a broad linear dynamic range for solution with pH value from 5.02 to 8.54.…”
Section: Ph-responsive Luminescent Materialsmentioning
confidence: 99%
“…The adjustment of ratio of fluorophore and surfactant within the LDH layer can effectively influence the fluorescence properties of guest molecules. Several fluorophores have been co-intercalated in the LDH layers, such as sulforhodamine B (SRB) [94], zinc phthalocyanines (ZnPc) [92], fluorescein (FLU) [106,107,136], ammonium 1-anilinonaphthalene-8-sulfonate (ANS) [137], and other similar systems (as shown in Table 8). The quantity of intercalated guest can be modulated through tuning the ratio of guest and surfactant, and the detailed information will be further introduced in Sect.…”
Section: Ion Exchangementioning
confidence: 99%
“…Shi et al have fabricated another pH sensor based on the co-intercalation of the fluorescein (FLU) and 1-heptanesulfonic acid sodium (HES), and the obtained samples exhibit good photo-and storage stability as well as high repeatability [101] toward responses of pH [106]. Employing electrophoretic deposition method, a sensor with broad linear dynamic range in pH (5.02-8.54) can be obtained (Fig.…”
Section: Detection Of Chemical Substancesmentioning
confidence: 99%
“…They have received much attention in the last 20 years due to their adjustable chemical composition, tunable charge density, anion exchange ability, and good thermal stability. 7,8 Because of their multi− functionalities, LDHs have been widely used in the areas of catalysis, 9−11 biochemistry, 12,13 adsorption, 14−16 anion exchange, 17 sensors, 18,19 polymer additives, 7,20−22 and so on.…”
Section: Introductionmentioning
confidence: 99%